رعاية التلاميذ ذوي الاحتياجات الخاصة - بلخيري, سليمة (جامعة الوادي - University of Eloued, 2019)
إن عملية الإدماج تتطلب رعاية تساعد التلاميذ من ذوي الاحتياج الخاص على تحقيق توافقهم كما تيسر تكيفهم النفسي والاجتماعي، وإن مفهوم الرعاية يلزمنا بضرورة توفير برامج ومعلمين بكفاءة تطابق احتياجات هؤلاء التلاميذ وتحقق الأهداف المطلوبة. ويأتي هذا المقال في محاولة للإحاطة بمفهوم الاحتياجات الخاصة باعتباره مفهوم يلقي بظلاله على شريحة كبيرة من الأفراد، وبالخصوص المتمدرسين منهم بهدف التعريف بهم وببرامجهم التعليمية ولبؤكد على ضرورة الرعاية الاجتماعية لهم بما تحمله من معاني تدلل على ضرورة توفير المساندة النفسية والمرافقة التربوية.Abstract: Special Education as an educational service aims to help pupils with special needs to achieve their compatibility and facilitate their psychological and social adjustment, and it obliges us to provide programs and teachers efficiently match the needs of these students and achieve the desired goals. This article comes in an attempt to take note of the concept of special needs as a concept that casts a shadow on a large segment of individuals, especially those who are educated with the aim of introducing them and their educational programs and stresses the need for social welfare for them with the meanings that demonstrate the need to provide psychological support and educational accompaniment.
مقال
Keywords: تربية خاصة ؛ فئات خاصة ؛ برامج تربوية ؛ معلم تربية خاصة ؛ رعاية اجتماعية ونفسية; Special education; special categories; educational programs; special education teacher; social and psychological care.